RMTool; Sebuah Aplikasi Pemodelan Persyaratan Perangkat Lunak menggunakan UML - Egia Rosi Subhiyakto; Danang Wahyu Utomo (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2017)
Requirement Engineering is one of stages in the software development. One of the challenges in requirements engineering is the use of tools in modeling the requirements. The number of requirements modeling applications does not guarantee that an analyst can model the needs appropriately for the complexity of the application, because the cost of modeling applications is too expensive to affect the use of such applications to model the requirements. Another problem faced by students on education is the difficulty in applying knowledge about software engineering. For example, if students are given a project from the industry, the requirements elicitation and modeling application are usually needed. The tools used in the industry are sometimes not suitable for education purposes. This paper aims to develop a tool for requirements modeling, to assist novice analyst in learning and classifying UML diagrams as well as learning the syntax. The tool is named RMTool, which is an object-oriented modeling tool based on web. Testing is conducted both on the developer and the user environment. Evaluation by end users involves 76 students as novice analyst to test the effectiveness and usefulness of modeling tool using questionnaire. The evaluation results show that the majority of students are satisfied using the application.